Pielonefritis en una gestante de 10 semanas - Acebo Suarez, Nathaly Silvana (2018)
Pregnant women easily develop urinary tract infections due to functional, hormonal and anatomical changes, as well as the location of the urethral meatus exposed to uropathogenic and vaginal bacteria that access the urinary tract and ascend through it and affect some organs. . For the nursing professional it is necessary to apply the care process, which is a work method that consists of a system as steps that are related to each other allowing to identify and satisfy the patient's needs and solve health problems. General Objective: Prepare a nursing care plan in a pregnant woman for 10 weeks with pyelonephritis to maintain the health of mother and child